The Influence Of Customer Reviews, Customer Ratings, Information Quality, And Price On Consumer Purchase Intention On The Shopee Online Market For Students SMK Negeri 1 Kota Bengkulu - Oktaviani, Nela; Hanila, Siti; Irawan Abi, Yudi (Journal of Management, Economic, and Accounting, 2024)
The aim of this research is to determine the influence of customer reviews, customer ratings, information quality and price on consumer buying interest in the Shopee online market among SMK Negeri 1 students in Bengkulu City. The sample in the study was 100 students at SMKN 1 Bengkulu City. Data were collected using a questionnaire and the analysis methods used were multiple linear regression, determination tests and hypothesis tests. The results of the regression analysis show Y = 1.737 + 0.236X1 + 0.236 X2 + 0.140X3+ 0.537X4+e. Customer reviews have a significant influence on consumer buying interest in the Shoppe online market for SMK Negeri 1 students in Bengkulu City with a significant value of 0.013, less than 0.05. Customer assessment has a significant influence on consumer buying interest in the Shoppe online market for SMK Negeri 1 students in Bengkulu City with a significant value of 0.039, which is smaller than 0.05. Information quality has a significant influence on consumer buying interest in the Shoppe online market among SMK Negeri 1 students in Bengkulu City with a significant value of 0.010, which is smaller than 0.05. Price has a significant influence on consumer buying interest in the Shoppe online market for SMK Negeri 1 students in Bengkulu City with a significant value of 0.000 which is smaller than 0.05. This illustrates that the cheaper product prices on the Shoppe online market are a consideration for SMK Negeri 1 students in Bengkulu City who are interested in making purchases. Customer reviews, customer ratings, information quality and price have a significant and joint effect on consumer buying interest in the Shoppe online market for SMK Negeri 1 students in Bengkulu City with a significant value of 0.000, which is less than 0.05.